SCHOOL CHEMISTRY COURSE BASED ON THE THEORY OF SYDOLOGY HYDROLYSIS INDICATORS - B.M.Abdurakhmanov; Sh..Sharipov; Gn. Sharipov; Sh. Giyosov (Galaxy International Interdisciplinary Research Journal, 2022)
This article presents the theoretical foundations of methods of implementation based on the theory of indicators in the study of salt hydrolysis processes, mainly in the formation of chemical concepts among students.